(Nie)topika Zagłady w Opowieściach zasłyszanych - Kuczyńska‑Koschany, Katarzyna (Narracje o Zagładzie [czasopismo zamknięte], 2016)
The (Non‑)topos of the Holocaust in Opowieści zasłyszane The article is a twofold attempt: at re‑reading the category of a topos after the Shoah and at interpreting the particular record of the oral history in the context of the liminal metamorphoses the notion of the topoi – crucial in European culture and literature – has undergone. In the first part of the text, the author recapitulates the studies on the aforementioned category – from Aristoteles to the twentieth century scholars (Curtius, Lausberg, Ziomek, Abramowska, Panas); in the second part, she tries to apply it in interpretative practice. Key words: topoi, oral history, rhetoric, Majdanek, gulag, non‑place